The Hardy Cross method and its implementation in Spain - Pons, Josep Maria (Lámpsakos (revista descontinuada), 2020)
In May 1930, Hardy Cross (1885-1959) published an article called ‘Analysis of continuous frames by distributing fixed-end moments’ in the American Society of Civil Engineers (ASCE). This article proposed a new approach to Structural Theory, and its relevance could be compared to that of the Three Moments Theorem (also known as the Clapeyron Theorem). The Cross method, as this calculation methodology has been often called, had remarkable significance from the moment it came out until the 70s, when new calculation methods became popular. In the present article, we will be trying to evaluate its impact in locations far from its origins; in particular, how it was understood and formulated in Spain. As will be demonstrated, the importance of this method was extremely relevant for the construction of new buildings and the implementation of new industries, which started to appear in a decisive moment for the development of the country. Even though the Hardy Cross method was the most widely used methodology at the time, two other procedures were also available; namely, the Kani and the Takabeya methods, methods that would also appear in the technical bibliography of the time. Despite the infrequent implementation of these other methods, we have briefly referred to both of them in the present paper. This article aims to show the relevance of the Cross method as well as its early implementation in Spain, by using academic bibliography of that time.